The effectiveness of the maintenance management system implementation for high-rise building / Nur Imanina Hadfina Abdul Halim ... [et al.] - Abdul Halim, Nur Imanina Hadfina; Mamat, Mohd Esham; Mamter, Shahela; Abdullah, Mohd Nazri (2022)
Building maintenance is required when the building is completed to keep it in good condition. Therefore, the best way to accomplish outstanding maintenance is to provide maintenance management that meets the user's anticipated demands as closely as possible. However, when it comes to building and infrastructure management and maintenance, we have many shortcomings, such as occupants living in high-rise buildings face several problems, disastrous defects as the roof collapses and can lead to injuries and accidents. Therefore, this research aim is to analyse the effectiveness of maintenance management toward high–rise building. In order to achieve the aim of the study, the objectives of this research are to identify the factors contributing to maintenance problem that faced in managing maintenance works, to determine the effect of unsystematic maintenance management toward high – rise building and to suggest the suitable solution to improve the maintenance management systems toward high – rise building. This study used a quantitative approach and questionnaire as the data collection instrument. The result indicates that one of the most significant contributors to the maintenance problems is insufficient budgets to efficiently run maintenance operations. Furthermore, the most major effect of unsystematic maintenance management that has been identified in this research is financial effect where it may have a huge effect on construction project progress. Thus, the suitable solution to improve the maintenance management systems is by having strict supervision for monitoring the construction sites so that remedial work can be carried out immediately.